Sanksi Pidana Merintangi Upaya Penanggulangan Kejadian Luar Biasa dan Wabah dalam Pembaruan Undang-Undang Kesehatan - Munandar, M. Aris; Pratiwi Arifin, Arnita; Khamila, Alya (Universitas Ekasakti, 2024)
The research method used in this article is normative legal research, with a statutory approach. This research aims to identify legal rules, legal principles, and legal doctrines that are relevant to the legal issues of overcoming extraordinary events and outbreaks, as well as to find the basis and ontological foundation behind the formation of certain laws, including the identification of the ratio legis. Criminal law policies against perpetrators of criminal acts, especially related to the handling of extraordinary events and outbreaks, have significant implications for the implementation of prevention efforts and the achievement of sustainable development goals, especially in the 3rd Sustainable Development Goals (SDG) related to sustainable health. Criminal sanctions must be clear and firm to ensure legal certainty for the community in accordance with the principle of legality. However, in Article 446 of the Health Law, there are deficiencies and vagueness in the formulation of articles that can hinder effective law enforcement, especially in emergency situations such as the Covid-19 pandemic. The ideal concept of punishment comprehensively considers the factors that influence criminal offenders, in line with the principles of justice and takes into account social and economic factors. Flexibility in the application of punishment, such as community service as an alternative to fines, can be more relevant and have a positive impact, especially in public health emergencies. Refinement and adjustment of criminal law policies are essential to support the management of extraordinary events and outbreaks and achieve sustainable development goals in the health sector.